2020
DOI: 10.1017/rdc.2020.136
|View full text |Cite
|
Sign up to set email alerts
|

RE-EVALUATING THE BRONZE AND EARLIEST IRON AGE IN LATVIA: CHANGES IN BURIAL TRADITIONS IN THE LIGHT OF 14C DATES

Abstract: Until recently, there was a lack of radiocarbon (14C) dates from the Bronze and Earliest Iron Age (1800–500–1 BC) burial sites in Latvia. The chronology of the sites was assessed on the basis of archaeological analogies with neighboring regions and typological studies of the rather meagre grave inventory. In order to establish a firm foundation for an absolute chronology of burial sites and to better understand changes in mortuary practices during the period, sequences of samples from various burial sites have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The cremation custom remained in use alongside inhumation throughout the region until the end of this period. Furthermore, one date yielded by a cremation burial in the Lazdiņi stone grave cemetery demonstrated that the cremation custom continued into the 3rd-1st century BC (201-46 cal BC) (Legzdiņa et. al 2020(Legzdiņa et.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cremation custom remained in use alongside inhumation throughout the region until the end of this period. Furthermore, one date yielded by a cremation burial in the Lazdiņi stone grave cemetery demonstrated that the cremation custom continued into the 3rd-1st century BC (201-46 cal BC) (Legzdiņa et. al 2020(Legzdiņa et.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent radiocarbon dates obtained from cremation burials in Latvia indicate that the spread of the cremation custom in the East Baltic region could have started between the 17th (16th) and 15th century BC, as evidenced by dates from the Pukuļi barrow cemetery in southern Latvia (Legzdiņa et al 2020(Legzdiņa et al , 1845(Legzdiņa et al -1868. Until recently, only six samples from cremation burials in flat cemeteries had been dated in Lithuania (Tamulynas 2004, 18;Piličiauskas 2012, 13, 16;Vengalis et al 2020, 37-38), and no radiocarbon dates had been obtained from barrows.…”
Section: Introductionmentioning
confidence: 99%
“…Kristian Kristiansen has proposed that changes in archaeological thought should be seen as a paradigm shift influenced by the third scientific revolution -a significant increase in the Big Data and especially the DNA research offered by the STEM disciplines [Kristiansen 2014]. In the case of Latvian archaeology, the contribution of natural sciences has indeed been significant in light of the recent discoveries [e. g., Legzdiņa, Vasks et al 2020]. Of course, we could argue with Kristiansen that this is not a revolution, but in fact a consistent, protracted and difficult path of research.…”
Section: Can Archaeologists Change the World?mentioning
confidence: 99%